(untitled) (LEGAL DIALOGICA, 2025)
This study aims to determine and analyze the settlement of disputes regarding the position of illegitimate children in the distribution of inheritance. As well as to determine and analyze the rights of illegitimate children from a legal perspective in Indonesia. This study is a type of normative legal research by examining library materials or legal materials. The results of this study indicate that 1) An illegitimate child has been legally recognized by his biological parents, so the legal relationship formed only applies between the child and the parent who gave the recognition. However, the child’s rights to inheritance remain limited. In practice, there are still normative obstacles because the Civil Code has not been fully adjusted to the spirit of the Constitutional Court Decision. An illegitimate child only has a legal relationship with his mother and his mother’s family. 2) Unless there is recognition from the father. An illegitimate child does not automatically have inheritance rights to his biological father, unless the father officially acknowledges that the child is his flesh and blood. ABSTRAK Penelitian ini bertujuan untuk mengetahui dan menganalisis penyelesaian sengketa terhadap kedudukan anak diluar nikah dalam pembagian warisan. Serta untuk mengetahui dan menganalisis hak bagi anak luar nikah dalam perspektif hukum di Indonesia. Penelitian ini ialah jenis penelitian hukum normatif dengan cara meneliti bahan pustaka atau bahan hukum. Hasil penelitian ini menunjukkan bahwa 1) Anak luar nikah telah diakui secara sah oleh orang tua biologisnya, maka hubungan hukum yang terbentuk hanya berlaku antara anak dan orang tua yang memberikan pengakuan tersebut. Akan tetapi, hak anak terhadap harta warisan tetap dibatasi. Dalam praktiknya masih terdapat kendala normatif karena KUH Perdata belum sepenuhnya disesuaikan dengan semangat Putusan MK. anak luar nikah hanya memiliki hubungan hukum dengan ibunya dan keluarga ibunya. 2) Kecuali jika ada pengakuan dari pihak ayah. Anak luar nikah tidak secara otomatis memiliki hak waris terhadap ayah biologisnya, kecuali ayah tersebut mengakui secara resmi bahwa anak tersebut adalah darah dagingnya.